Parent’s Role on Accesability Service for Disabled Family Member - Ikawati, Ikawati (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The research was done to know the parent (with disabled) role on information, communication, education, health, job opportunity, social assurance, sport facility, culture, recreation, and leisure, building network, mobility services, in emergency situation and law protection service, and political participation. Research location was in Pasuruan regency, East Java province. Respondents ditermined purposively, families with disabled member, it was found 35 respondents. Data gathered through interview and observation, and analyzed through qualitative technique. Based on the finding it can be concluded that the parent role on the disabled member of the family has yet maximum, because of lack socialization from related institution on the access for disabled. The limit of education, knowledge, economic know-how, caused parents suffering from limitation to access services. It recommended that related institutions should enhance its program socialization to community, especially to family with disabled member so that they can access the services. To the Ministry of Social Affairs, especially through the General Directorate of Social Rehabilitation (for disabled), the institution should empower families especially those with disabled members, through counseling, guidance, enhancement awarnessand parents capacity on taking care of problem, potentiality, resource, and disabled needs,including empowerment on family economy or entrepreneurship.